From Beckett to Havel: Absurdist Playwrights of Western and Central Europe Compared - P. Müller, Péter (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The creator of the term of the absurd drama, Martin Esslin (who was born in Budapest, Hungary) published his book The Theatre of the Absurd in 1961. The term he used to characterize a trend in then contemporary drama soon became popular and mis-used. Esslin felt it important to draw attention to the sense in which he had intended to use the term. In the preface to the 1968 edition of his book, he stressed that the term of the Theatre of the Absurd was only a working hypothesis, a concept to give basis for the comparative analysis. “How could that have led to the assumption that Beckett and Ionesco should behave towards each other as members of the same club or party? Or that Pinter subscribed to the same views on politics or law as Genet? Only by profound misunderstanding” (Esslin, Theatre 12).